Diseño y simulación de un sistema de monitoreo para un proceso de control de temperatura mediante PLC e IoT para la empresa Educatia (2021)
Throughout history the human being has looked for a way to evolve, we have observed that the industrial revolutions have meant change of the way of life, the invention of machines that develop beer products and that every day they do it faster, it has also meant that every day people grow academically to meet these technological challenges in industries, the fourth revolution not only specifies that industrial processes must be faster and efficient but also smart, autonomous and have constant feedback and that they can make decisions that generate better practices in the process.